International norm development and change: can international law play a meaningful role in curbing the lifestyle disease pandemic? - Preslava Stoeva (BMC, 2020)
Abstract Background The magnitude of the noncommunicable epidemic is difficult to overstate. The projected cost of the epidemic is substantial. It disproportionately affects people in low- and middle-income countries as well as poorer and marginalised communities in high-income countries. The international community has taken various steps to address the four modifiable risk factors causing the majority of noncommunicable diseases (NCDs), however, action has so far fallen short of expectations. Both analysts and international institutions are advocating the adoption of a new international legal norm to address the NCD crisis. Main text Drawing on existing knowledge from international relations and international legal studies, this article argues that a new international treaty is not only currently improbable, but also not strictly desirable. In-depth critical analysis and reflection is needed regarding the strengths and weaknesses of a legal approach to addressing the NCD pandemic. The argument is set out in three sections - the first reviews contributions of agentic constructivism, which focus on the process of normative emergence and change, and draws on empirical examples to highlight overlooked aspects of normative development and how they relate to NCD politics. The second engages with the critique of legal principles. Critical approaches to law seek to expose the myths that legal principles are neutral, objective, good. The third section discusses the characteristics of practice in the NCD field and its implications on process and principles for the pursuit of a legal solution to the NCD crisis. Conclusions Any advocacy for an international norm to address NCDs needs to be nuanced and demonstrate awareness of the nature and character of both the norm development process and resulting international legal principles. As analysts, we are responsible for advocating inclusive and ethical norms, but also for highlighting the implications of inequalities and differences between and within states and societies. There may be a viable international legal instrument that would support dedicated policies to curb the NCD epidemic, but such an instrument needs to be actively advocated for and negotiated with a wide range of stakeholders, navigating a complex international framework of existing norms and conflicting, powerful interests.